KONTRIBUSI IKLIM KOMUNIKASI DAN MOTIVASI BERPRESTASI TERHADAP KEPUASAN KERJA GURU MTSN LANGSAT KADAP RAO PASAMAN - Faizah Faizah (IAIN Batusangkar, 2016)
The Contributions climate communication and achievement motivation toward jobsatisfaction teachers of MTsN Langsat Kadap Rao Pasaman. This study is aimed at identifying anddescribing the direct influence of: (1) to determinase whether there is a achievement communationclimate contribution toward work satisfaction of teachers MTsN Langsat Kadap Rao Pasaman. (2)to determinase whether there is a achievement achievement motivation contribution toward worksatisfaction of teachers MTsN Langsat Kadap Rao Pasaman. (3) to determinase whether there is aachievement communication climate and achievement motivation contribution simultaneously towardwork satisfaction of teachers MTsN Langsat Kadap Rao Pasaman.This study used quantitative methodswith two-way analysis variance. The population were all junior high school teachers in SipoholonDistrict of North Tapanuli numbered 60 persons and sample 32 persons which were determined byproportional stratified sampling technique. The data was collected by using the instrument. Priorto testing the hypothesis, the normality of the data was tested by using correlation, linearity andregression equations test were used by anava and homogeneity was tested by Bartlett test. The resultsshow that the variable of communication climate and achievement motivation can be used as a factorin determining the performance of MTsN Langsat Kadap Rao Pasaman.Kata Kunci: Iklim komunikasi, motivasi berprestasi, kepuasan kerja guru.